An Analysis of the Experiential Function in Motivational Dialogue from the Movie “Barbie” (2023): A Discourse Analysis - Pohan, Rizqina Fauziah; Gultom, Qaila Zulhairah; Ajizah, Aulya; Rangkuti, Linda Astuti; Sihite, Meida Rabia (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
The objective of this study is to investigate whether the motivational dialogue from the movie